(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indian Monsoon Rainfall is a gamble for the Indian farmers and the policymakers in terms of variability. Rainfall is a main role player in the Indian economy &agricultural productivity. Uneven variability of rainfall is the main cause behind thelacking economical condition of Indian farmers besides that it is also the challengebefore the governing authority to plan for the regional imbalance. We are trying toevaluate the reciprocity of Indian Monsoon and the agricultural yield and productionthroughvarious ways.